OP0149 VISUAL LOSS IN PATIENTS WITH GIANT CELL ARTERITIS TREATED WITH TOCILIZUMAB. (2nd June 2020) - Amsler, J.; Kysela, I.; Christ, L.; Tappeiner, C.; Seitz, L.; Scholz, G.; Kollert, F.; Reichenbach, S.; Villiger, P.
Abstract : Background: Whether Tocilizumab (TCZ) may prevent vision loss in Giant Cell Arteritis (GCA) to the same extent as glucocorticoids remains a key and unanswered question. A patient cohort observed over up to 8 years addresses this issue. Objectives: To investigate the frequency of vision loss/visual impariment in a GCA cohort treated with TCZ. Methods: In this observational monocentric study, the courses of 192 patients with GCA treated with TCZ between 01.01.2011 and 31.12.2018 were analyzed. Data were extracted from medical records and collected in a Clinical Trial Unit (CTU) - based registry. Demographic, clinical and laboratory data were analyzed. Results: 192 patients with GCA were treated with TCZ; 121 (63%) were female, 112 (58%) fulfilled 1990 American College of Rheumatology (ACR) criteria, all others had large vessel vasculitis based on magnetic resonance-angiography (MRA). The cumulative duration of TCZ treatment was 3467 months; the median treatment duration was 13.8 (8.5; 22.8) months. At baseline, visual impairment was present in 71 (37%) and vision loss in 21 (7.8%) patients. Visual loss was associated with higher age (74 (70; 82) vs. 70 (63; 76) years; p=0.029), lower C-reactive protein at baseline (14.0 (3.5; 42.0) vs. 54.5 (21.0; 101.0) mg/l; p<0.001), cranial symptoms (p<0.0001), jaw claudication (p=0.030) and negative MRA of the aorta (p=0.020). Over the observed time span only one patient taking part in a clinical trial developed vision loss. In total 4 (2%) patients with vision impairment showed deterioration and 61 (32%) improvement. Conclusion: Collectively, our data suggest that TCZ is able to prevent visual loss and may have a favorable effect on visual impairment. Disclosure of Interests: Jennifer Amsler: None declared, Iveta Kysela: None declared, Lisa Christ Consultant of: BMS, Christoph Tappeiner: None declared, Luca Seitz: None declared, Godehard Scholz: None declared, Florian Kollert Employee of: Novartis, Stephan Reichenbach: None declared, Peter Villiger Consultant of: MSD, Abbvie, Roche, Pfizer, Sanofi, Speakers bureau: Roche, MSD, Pfizer